Complicated complicity European collaboration with Nazi Germany during World War II - Bitunjac, Martina 1981-; Schoeps, Julius H. 1942- (De Gruyter Oldenbourg, 2021)
Complicated Complicity is about the forms taken, motives and spectrum of actions of European collaboration with the Nazis. State authorities, local military organizations and individual players in different countries and areas including France, Scandinavia, Lithuania, Poland, Ukraine, Romania, Hungary, Slovakia, Greece, Italy, Portugal and the countries of the former Yugoslavia are discussed in the context of the history of World War II, the history of occupation and everyday life and as an essential influencing factor in the Holocaust. New forms of right-wing populism, nationalism and growing intolerance of Jewish fellow citizens and minorities have made such historically sensitive studies considerably more difficult in many countries today. In this time of increasing historical revisionism in Europe, such elucidating discourse is particularly relevant
Beiträge der Konferenz "Collaborationism with Nazi Germany. A European Controversy" in Rom 2019 wurden um weitere Beiträge zum Thema ergänzt.
Keywords: Geschichte 1939-1945; Holocaust; Kollaboration; Zweiter Weltkrieg; HISTORY / Europe / Germany; Drittes Reich; Deutschland; Europa; Konferenzschrift -- 2019 -- Rom